2011
DOI: 10.1126/science.1204673
|View full text |Cite
|
Sign up to set email alerts
|

Sr-Nd-Pb Isotope Evidence for Ice-Sheet Presence on Southern Greenland During the Last Interglacial

Abstract: To ascertain the response of the southern Greenland Ice Sheet (GIS) to a boreal summer climate warmer than at present, we explored whether southern Greenland was deglaciated during the Last Interglacial (LIG), using the Sr-Nd-Pb isotope ratios of silt-sized sediment discharged from southern Greenland. Our isotope data indicate that no single southern Greenland geologic terrane was completely deglaciated during the LIG, similar to the Holocene. Differences in sediment sources during the LIG relative to the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
150
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(176 citation statements)
references
References 27 publications
21
150
0
Order By: Relevance
“…Taking contributions from thermal expansion and mountain glaciers into account and that global sea level was at least 6 m higher than today (Dutton et al, 2015), this implies that a contribution is likely also required from the WAIS (noted specifically by Colville et al, 2011) and/or other parts of the Antarctic ice sheet. Although studies have suggested the possibility of an East Antarctic contribution (Bradley et al, 2012;Fogwill et al, 2014;Pingree et al, 2011), this has yet to be quantitatively supported by observational or modelling evidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking contributions from thermal expansion and mountain glaciers into account and that global sea level was at least 6 m higher than today (Dutton et al, 2015), this implies that a contribution is likely also required from the WAIS (noted specifically by Colville et al, 2011) and/or other parts of the Antarctic ice sheet. Although studies have suggested the possibility of an East Antarctic contribution (Bradley et al, 2012;Fogwill et al, 2014;Pingree et al, 2011), this has yet to be quantitatively supported by observational or modelling evidence.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of the Greenland ice sheet to global LIG sea level rise has recently been quantified (Born and Nisancioglu, 2012;Colville et al, 2011;Helsen et al, 2013;NEEM community members, 2013;Quiquet et al, 2013;Stone et al, 2013), with the IPCC Fifth Assessment Report stating a range very likely between 1.4 and 4.3 m of equivalent sea level height . Taking contributions from thermal expansion and mountain glaciers into account and that global sea level was at least 6 m higher than today (Dutton et al, 2015), this implies that a contribution is likely also required from the WAIS (noted specifically by Colville et al, 2011) and/or other parts of the Antarctic ice sheet.…”
Section: Resultsmentioning
confidence: 99%
“…From the NEEM record (Dahl-Jensen et al, 2013), it is inferred that at 122 ka BP, the surface elevation thinned by 130 ± 300 m. The other five ice core sites remained ice covered, including Dye-3 (Yau et al, 2016). Additionally, analysis of Sr-Nd-Pb isotope ratios in offshore material collected from Erik Drift (Colville et al, 2011) infers that the southern margin retreated to a smaller extent than in the PD but that the ice sheet did not undergo complete deglaciation during the LIG.…”
Section: Observational Datamentioning
confidence: 99%
“…During the previous interglacial, when boreal summer temperatures were up to 58C warmer than at present, a smaller GrIS contributed 2 m to a global-mean sea level that was at least 4 m higher than that of today (Colville et al 2011;Dahl-Jensen et al 2013). On multimillenial time scales, large future volume changes of the GrIS will probably be controlled by the feedback between surface elevation and surface temperature (Levermann et al 2013).…”
Section: Introductionmentioning
confidence: 99%